2019
DOI: 10.1017/pen.2019.1
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated amygdala activity: an auto-biological index of affective distress

Abstract: Auto-biological beliefs—beliefs about one’s own biology—are an understudied component of personal identity. Research participants who are led to believe they are biologically vulnerable to affective disorders report more symptoms and less ability to control their mood; however, little is known about the impact of self-originating beliefs about risk for psychopathology, and whether such beliefs correspond to empirically derived estimates of actual vulnerability. Participants in a neuroimaging study (n = 1256) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…While there are a number of possible explanations, this null effect is not unprecedented. Three recent large-sample studies (Duke Neurogenetics Study: n = 1,256; HCP: n = 319; Minnesota Twin Study: n = 548) failed to detect credible relations between amygdala reactivity to threat-related faces and individual differences in negative emotionality (MacDuffie, Knodt, Radtke, Strauman, & Hariri, 2019; Silverman et al, 2019; West, Burgess, Dust, Kandala, & Barch, in press ). Does this mean that the amygdala, BST, and PAG are unrelated to negative affect?…”
Section: Discussionmentioning
confidence: 99%
“…While there are a number of possible explanations, this null effect is not unprecedented. Three recent large-sample studies (Duke Neurogenetics Study: n = 1,256; HCP: n = 319; Minnesota Twin Study: n = 548) failed to detect credible relations between amygdala reactivity to threat-related faces and individual differences in negative emotionality (MacDuffie, Knodt, Radtke, Strauman, & Hariri, 2019; Silverman et al, 2019; West, Burgess, Dust, Kandala, & Barch, in press ). Does this mean that the amygdala, BST, and PAG are unrelated to negative affect?…”
Section: Discussionmentioning
confidence: 99%
“…Although these are potentially interesting findings, they are primarily based on the association between observed changes in brain signal variability and the individuals’ subjective self-reported mental states. In this respect, a study by MacDuffie et al [ 206 ] that included 1256 human subjects concluded that such self-report ratings were unrelated to measured neural activation. The effect of this shortcoming can be indeed observed in meditation and mediated social communication studies.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we were not able to verify whether the observed changes in the cortical flow of information was due to the significantly different mindset of HIGH versus LOW groups (i.e., as far as their subjective responses to the questionnaires were concerned) or it rather captured a substantial change in the brain functions whose gradual effect could be traced along the stress-effect spectrum. Considering the findings that identified the individuals' subjective ratings to best predict their distress across a variety of self-report measures [108], future research can broaden the scope of the present study to the case in which individuals with broader stress responses are included. This, in turn, can allow for more informed conclusion on generalizability of observed differences between HIGH and LOW stress-susceptible groups to more inclusive scenario in which wider range of stress responses are considered.…”
Section: Limitations and Future Directionmentioning
confidence: 99%
“…STAI-G-X2 consists of 20 items that are rated using a four-point Likert scale, ranging from 1 (almost never) to 4 (nearly always). It is worthy of note that our approach to selecting the individuals based on their responses to questionnaires was motivated by a recent study by MacDuffieet et al [ 108 ] (1256 human subjects) in which the authors reported that individuals’ subjective ratings were the best predictors of their distress across a variety of self-report measures. They further concluded that such measures may represent informative indicators of individuals’ psychological function.…”
Section: Appendix A1 Determination Of Participants’ Stress-susceptimentioning
confidence: 99%